Dimeric dipeptide mimetics of the nerve growth factor loops 3 and 4 are active in a model of ischemic stroke - P. Y. Povarnina; T. A. Gudasheva; S. B. Seredenin (LLC "Publisher OKI", 2016)
Pharmacological activity of dimeric dipeptide mimetics of the nerve growth factor loops 3 and 4, correspondingly GTS-115 and GK-2, was studied in a model of ischemic stroke, induced by transient middle cerebral artery occlusion in rats. The both compounds, at i.p. subchronic administration (0,5-1 mg/kg/day, 7 days, beginning at 4 hours after surgery), significantly reduced cerebral infarct volume as was estimated by morphometry of 2,3,5-triphenyltetrazolium chloride (TTC) -stained brain slices: GTS-115 by 25% and GK-2 by 35%. Mimetic of NGF loop 4 (GK-2), which is the most active compound, was selected for further development as a potential therapeutic agent.